Estudios acústicos en poblaciones argentinas de Leptodactylus (Anura, Leptodactylidae): revisión histórica y datos adicionales - Zaracho, Víctor Hugo (2023)
The first systematized acoustic studies in Argentinean anuran populations began in the 1960s with the contributions made by Avelino Barrio. Since then, with some exceptions, the knowledge about the vocalizations of local species has had little development. Leptodactylus is a neotropical frog genus with 83 recognized species, 14 of which are found in Argentina. In this context, and with the aim of contribute to the acoustic knowledge about the anuran species that occur in Argentina, a review of the vocalizations of Leptodactylus species was addressed, with emphasis in local populations. Additionally, this information is compared with new acoustic data for L. bufonius, L. elenae, L. fuscus, L. gracilis, L. laticeps, L. latinasus, L. luctator, L. macrosternum and L. podicipinus obtained in populations from Corrientes, Chaco and San Juan provinces. Moreover, some terms used in previous studies are reviewed in order to standardize the terminology applied to the calls of Leptodactylus species. The absence of descriptions about vocalizations from topotypic populations is also noted, of which L. elenae, L. laticeps, and L. luctator have their type locality in Argentina. Studies on acoustic variation in anuran amphibians, whether for taxonomic or geographic variation purposes, can be considered incipient in Argentina, and therefore, there are still an important information gap. Comparisons of the acoustic variables of the advertisement call between different populations allow us to understand how the acoustic variables vary according to the environmental or geographical factors. Furthermore, the recordings of other types of calls contribute to increase the information about the acoustic repertoires and have a comprehensive knowledge about aspects of the natural history and behavior of the species. Finally, it is important to highlight the need for additional acoustic studies on anuran amphibians from Argentina, especially due to the continuous alteration or loss of their habitats, and consequently of the acoustic diversity and soundscape.